Effects of nutritional vitamin D supplementation on markers of bone and mineral metabolism in children with chronic kidney disease. Issue 12 (21st February 2018) - Lerch, Christian; Shroff, Rukshana; Wan, Mandy; Rees, Lesley; Aitkenhead, Helen; Kaplan Bulut, Ipek; Thurn, Daniela; Karabay Bayazit, Aysun; Niemirska, Anna; Canpolat, Nur; Duzova, Ali; Azukaitis, Karolis; et al.
ABSTRACT: Background: We investigated the effects of nutritional vitamin D supplementation on markers of bone and mineral metabolism, i.e. serum levels of fibroblast growth factor 23 (FGF23), Klotho, bone alkaline phosphatase (BAP) and sclerostin, in two cohorts with chronic kidney disease (CKD). Methods: In all, 80 vitamin D–deficient children were selected: 40 with mild to moderate CKD from the ERGO study, a randomized trial of ergocalciferol supplementation [estimated glomerular filtration rate (eGFR) 55 mL/min/1.73 m 2 ], and 40 with advanced CKD from the observational Cardiovascular Comorbidity in Children with Chronic Kidney Disease (4C) study (eGFR 24 mL/min/1.73 m 2 ). In each study, vitamin D supplementation was started in 20 children and 20 matched children not receiving vitamin D served as controls. Measures were taken at baseline and after a median period of 8 months. Age- and gender-related standard deviation scores (SDSs) were calculated. Results: Before vitamin D supplementation, children in the ERGO study had normal FGF23 (median 0.31 SDS) and BAP (−0.10 SDS) but decreased Klotho and sclerostin (−0.77 and −1.04 SDS, respectively), whereas 4C patients had increased FGF23 (3.87 SDS), BAP (0.78 SDS) and sclerostin (0.76 SDS) but normal Klotho (−0.27 SDS) levels. Vitamin D supplementation further increased FGF23 in 4C but not in ERGO patients. Serum Klotho and sclerostin normalized with vitamin D supplementation in ERGO but remained unchanged in 4C patients. BAP levels were unchanged in all patients. In the total cohort, significant effects of vitamin D supplementation were noted for Klotho at eGFR 40–70 mL/min/1.73 m 2 . Conclusions: Vitamin D supplementation normalized Klotho and sclerostin in children with mild to moderate CKD but further increased FGF23 in advanced CKD.